Effects of temperature and water purity on germination and yield of mungbean sprouts - Hanif, Muhammad; Khattak, Mansoor Khan; Ul Haq, Inam; Gul, Kausar; Khan, Ansa; Ullah, Kaleem; Khan, Ali; Ali, Azmat (Penerbit Universiti Kebangsaan Malaysia, 2019)
Mungbean (Vigna radiata L. Wilczek) is a popular pulse crop, producing protein-rich food and nitrogen-rich residues. Mungbean sprouts were grown at different temperature levels of 10, 20 and 30°C in various water purities of 30 (distilled water), 100, 400, 700 and 1000 TDS (ppm). After keeping them in the germination chamber for 72 h, the percentage of germination, stem length and yield along with proximate composition were determined. The temperature was kept as main factor and water purity as the second. The experiment was replicated four times and the data obtained were analyzed using two factorial completely randomized design. The results showed that both the factors had significant (p<0.05) effect on the germination, stem length, yield as well as proximate composition. A temperature of 30°C and water with high purity of 30 TDS resulted in high emergence (69%), stem length (3.14 cm) and yield (70.1 g) as compared to the other treatments. Minimum germination (2.1%), stem length (0.11 cm) and yield (12.11 g) were recorded in samples kept at low temperature of 10°C and water purity with 1000 TDS. The mungbean seeds showed a very low plasticity to water purity, and that they were very susceptible to water impurities. It is concluded that, to prepare sprouts from mungbeans, it is necessary to germinate mungbean seeds them in water having high purity and temperature of 30oC for maximum germination, stem length and yield.